PENENTUAN BILANGAN REYNOLD DAN FROUDE, REDESIGN ZONA SEDIMENTASI RECTANGULAR DENGAN PLATE SETTLER DAN TUBE SETTLER, WATER TREATMENT PLANT (WTP), KAWASAN INDUSTRI DAN PERUMAHAN “X”, KABUPATEN BEKASI - Aris Dwi Cahyanto; Ilyas Nur Ilman; Armen Putra (Politeknik Negeri Jakarta, 2023)
Sedimentation is the separation between solids and solutions with the force of gravity. To improve the performance and efficiency of sedimentation tanks, it can be done by adding a device, namely pseudo base, plate settler, or tube settler. The purpose of this study is to modify rectangular sedimentation zones with plate settlers and tube settlers in the Water Treatment Plant (WTP) and analyze the flow that occurs in the sedimentation zone by examining Reynold numbers (NRE) and Froude numbers (NFR). To achieve this goal, the authors conducted field observations on the sedimentation unit in the Industrial Water Treatment Plant and